Effects of Transcranial Alternating Current Stimulation and Neurofeedback on Alpha (EEG) Dynamics: A Review - Orendáčová, Mária; Kvašňák, Eugen (Frontiers in Human Neuroscience, 2021)
Transcranial alternating current stimulation (tACS) and neurofeedback (NFB) are two different types of non-invasive neuromodulation techniques that can modulate brain activity to improved brain functioning. In this review, we compared current state of knowledge regarding mechanisms and effects of tACS and NFB on EEG activity (online period/stimulation period) and on aftereffects (offline period/post/stimulation period) including duration of their persistence and potential behavioral benefits. Since alpha band-width has been broadly studied in NFB as well as in tACS research, NFB and tACS studies modulating alpha bandwidth were selected for comparing online and offline effects of these two neuromodulation techniques. Factors responsible for variability in responsiveness of modulated EEG activity to tACS and NFB were analyzed and compared too. Based on the current body of literature related to tACS and NFB, it can be concluded that tACS and NFB differ a lot in mechanisms responsible for their effects on online EEG activity but they possibly share a common universal mechanisms responsible for induction of aftereffects in targeted stimulated EEG band, namely, Hebbian and homeostatic plasticity. Many studies of both neuromodulation techniques report aftereffects connected to behavioral benefits. Their duration of persistence is comparable for NFB and tACS. In relation to factors influencing responsiveness to tACS and NFB, significantly more types of factors were analyzed within NFB studies compared to tACS studies. Several common factors have been already investigated for both tACS and NFB. Based on these outcomes, we propose several new research directions regarding tACS and NFB.